Financial feasibility study of object development flower garden tourism in telaga kodok village - Restia Christianity; Muhammad Faisal; Erfendi Regar (Institute of Computer Science (IOCS), 2024)
Indonesia is an archipelagic country that has a variety of cultures and tourism. Tourist attractions are a feature of introducing the culture and image of an area. By promoting the tourism industry, an area can create new jobs and provide more economic opportunities. One of the areas used as a tourist destination in Maluku is Telaga Kodok Village in Central Maluku Regency. Telaga Kodok Village has the potential for Organic Agriculture and is being prepared to be developed into an Agrotourism Village and Organic Learning Center. Currently the products produced are organic vegetable and fruit cultivation, flower garden tourism, organic pesticides and compost fertilizer. Tourism in Telaga Kodok Village can also be used as a role model through managing the planting process until post-harvest. Tourism development at tourist attractions in Telaga Kodok Hamlet with its natural beauty in the form of agricultural tourism for marine tourism education and tourist attractions in the form of flower plantations. Tourist attraction is a force to attract tourists. An object has the potential to become a tourist attraction or tourist attraction, but to make the object attractive requires other elements such as accessibility and supporting facilities as well as the environment around the object that supports it. The aim of this research is to determine the development of tourist attractions in the development of tourist attractions in Telaga Kodok Hamlet, using a descriptive qualitative approach. The data collection technique in this research is triangulation of data obtained from interviews, document study and observation. The output of this research is a reputable national journal.